The Effect of Monetary Instrument of Islamic Banking Financing Channel Towards The Economic Growth in Indonesia - Johari, Sobar M.; Wong, Wing Keung; Anjasari, Ida Fitri; Ha, Nguyen Tran Thai; Thuong, Trinh Thi Huyen (Jurnal Ekonomi & Studi Pembangunan, 2022)
Monetary policy is closely related to activities to achieve economic growth, which eventually gives welfare to the community. This study aims to analyze the description of the transmission flow of financing channels, the effect of monetary policy instruments, and their effectiveness to achieve economic growth. The variables used are Islamic Banking Finance (FIN), return of Sharia Bank Indonesia Certificate (SBIS), return of PUAS, and Industrial Production Index (IPI). This study used Vector Error Correction Model (VECM) to determine short- and long-term relationships using the time series data. First, the result of the study showed that the transmission flow could not be identified clearly, because the flow stopped in FIN, and it could not affect IPI, according to the Granger Causality test. Second, the result of VECM estimation showed that all variables only affected long term period and did not affect the short-term period. Third, monetary policy transmission of Islamic banking financing channel was not effective enough, which was proven with the result of IRF simulation, which showed that the effect of shock on financing channel variable (FIN) towards IPI was subsided and stable in the 10th period later. Meanwhile, the result of the FEVD simulation showed that the financing channel variable (FIN) only gave a contribution of as much as 0.14 percent towards IPI. The contribution and policy implications are also discussed in this study.